Pengaruh Corporate Social Responsibility, Millennial Leadership, Gender Diversity terhadap Nilai Perusahaan. : Studi Empiris Perusahaan Index LQ-45 Periode 2017-2020 - Temy Setiawan (Owner : Riset dan Jurnal Akuntansi, 2022)
One measure of the success of a company is seen from the value of the company through 3 non-financial factors, namely CSR, Millennial Leadership, Gender Diversity. This study uses the LQ45 Index company for the 2017-2020 period with a sample of 120 data from 30 companies. The sample used was purposive sampling method with the analytical method using SPSS 26. The results of this study found that CSR and millennial leadership had an effect on the true value of the company, respectively 0.02 and 0.07. Meanwhile, for gender diversity, the results have no effect on firm value. And in this study, it can only explain the variance of the dependent variable of 10.10%.